Cardiometabolic multimorbidity may identify a more severe subset of rheumatoid arthritis, results from a "real-life" study. Issue 14 (7th April 2023) - Ruscitti, Piero; Di Muzio, Claudia; Conforti, Alessandro; Di Cola, Ilenia; Pavlych, Viktoriya; Navarini, Luca; Currado, Damiano; Biaggi, Alice; Di Donato, Stefano; Marino, Annalisa; Lorusso, Sebastiano; Ursini, Francesco; et al.
Abstract : This "real-life" cross-sectional study has been designed to describe disease features of rheumatoid arthritis (RA) participants affected by cardiometabolic multimorbidity than those without. Our purpose was also the identification of possible associations between these cardiometabolic diseases and RA clinical characteristics. Consecutive RA participants with and without cardiometabolic multimorbidity were assessed and their clinical characteristics were recorded. Participants were grouped and compared by the presence or not of cardiometabolic multimorbidity (defined as ≥ 2 out of 3 cardiovascular risk factors including hypertension, dyslipidemia, and type 2 diabetes). The possible influence of cardiometabolic multimorbidity on RA features of poor prognosis was assessed. The positivity of anti-citrullinated protein antibodies, presence of extra-articular manifestations, lack of clinical remission, and biologic Disease-Modifying anti-Rheumatic Drugs (bDMARDs) failure were considered as RA features of poor prognosis. In the present evaluation, 757 consecutive RA participants were evaluated. Among them, 13.5% showed cardiometabolic multimorbidity. These were older ( P < .001) and characterized by a longer disease duration ( P = .023). They were more often affected by extra-articular manifestations ( P = .029) and frequently displayed smoking habit ( P = .003). A lower percentage of these patients was in clinical remission ( P = .048), and they showed a more frequent history of bDMARD failure ( P < .001). Regression models showed that cardiometabolic multimorbidity was significantly correlated with RA features of disease severity. They were predictors of anti-citrullinated protein antibodies positivity, of extra-articular manifestations, and of lack of clinical remission, in both univariate and multivariate analyses. Cardiometabolic multimorbidity was significantly associated with a history of bDMARD failure. We described disease features of RA participants with cardiometabolic multimorbidity, identifying a possible more difficult to treat subset, which may need a new management approach to achieve the treatment goal.